Minimalisasi Interferensi Dengan Metode Open Loop Power Control Pada Jaringan Femtocell Uplink FDD LTE-Advanced - Irmayani Irmayani; Ishar Zulfika (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract LTE-Advanced have a feature femtocell or often called HeNB in standard 3GPP release 10 which has low transmit power in indoor. On the other hand, the HeNB is causing interference that occurs due to the use of communication channel together between user HeNB and eNB in the same time either in uplink or downlink direction. Interference uplink direction occurs between HUE (Home User Equipment) or between HUE and MUE (Mobile User Equipment). The open loop power control method is used to minimize uplink interference on LTE-Advanced system with femtocell. This method minimizes the power of the interference so that interference power on eNB and HeNB decreases and the value of system performance parameters improves. From the results of the tests performed, the open loop power control method effectively minimizes interference with proven power interferences that decreased significantly both in eNB and HeNB. The average value of MUE interference power to HeNB is 1.73E-18, 5.46E-18, and 1.29E-06. Furthermore,the average value of HUE interference power to heNB is 1.58E-04, 5.26E- 05, and 5.43E- The decrease in interference power affects system performance such as SINR, throughput, spectralefficiency, and Eb / No. The open loop power control method was applied, the average percentage range of SINR above 30 dB was 13% - 100%. Then the average percentage range of throughput values above 2 Mbps is 70 - 100%. Then the average percentage range of spectral efficiency values above 10 bps / Hz is 13% - 43%. Then the average percentage range Eb / No above 20 dB is 13-100%. The system there is an increase in performance by 45% Keywords: Femtocell, Interference, LTE, LTE-Advanced, Open Loop Power Control